Consider the function f, where f(x) = 2x^2 - x + 3 . The function g is modeled by the equation g(x) =3 . What are the solutions to function g and function f where, g(x) = f(x) ?

Respuesta :

Answer:

0 and 0.5 are the solutions to the equation f(x) = g(x)

Step-by-step explanation:

We are going to equate two functions and find the value of x at which both the function values are equal. In other words, we find the points where the graphs of both the functions coincide. This is because at this point the function values coincide.

f(x) = [tex]2x^{2} - x + 3[/tex]

g(x) = 3

Now we are going to equate f(x) = g(x)

[tex]2x^{2} - x + 3[/tex] = 3

[tex]2x^{2} [/tex] = x

x(2x - 1) = 0

x = 0 or x = 0.5 are the solutions of the equation f(x) = g(x)